2016
DOI: 10.1787/5jln7dlm3931-en
|View full text |Cite
|
Sign up to set email alerts
|

Services Trade Restrictiveness, Mark-Ups and Competition

Abstract: This report explores the relationship between services trade policies and markups at the firm level, taken as a measure of competitive pressure. Restrictive regulations are found to enable firms to charge higher markups in a majority of services sectors, suggesting ample scope for pro-competitive gains from trade liberalisation. Barriers to establishment consistently enable incumbent firms shielded from competition to raise their prices, while a lack of regulatory transparency and complex administrative proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Although these findings might seem surprising, earlier estimates of the effects that the STRI has on services trade have also identified at times stronger negative impacts on exporters than on importers (Nordås and Rouzet, 2015). A plausible explanation for this result could be that restrictions to services trade at home make domestic firms less competitive than their foreign counterparts, in particular where those restrictions take the form of anti-competitive regulations hindering the entry of new competitors, or where regulatory burdens raise the operating costs of firms operating in the exporting country (Rouzet and Spinelli, 2016). In the present context, services restrictions at home may increase the cost of services used as inputs in the environmental industry, thereby causing domestic providers of environmental services to be at a disadvantage relative to foreign competitors.…”
Section: Detailed Results and Caveatsmentioning
confidence: 98%
“…Although these findings might seem surprising, earlier estimates of the effects that the STRI has on services trade have also identified at times stronger negative impacts on exporters than on importers (Nordås and Rouzet, 2015). A plausible explanation for this result could be that restrictions to services trade at home make domestic firms less competitive than their foreign counterparts, in particular where those restrictions take the form of anti-competitive regulations hindering the entry of new competitors, or where regulatory burdens raise the operating costs of firms operating in the exporting country (Rouzet and Spinelli, 2016). In the present context, services restrictions at home may increase the cost of services used as inputs in the environmental industry, thereby causing domestic providers of environmental services to be at a disadvantage relative to foreign competitors.…”
Section: Detailed Results and Caveatsmentioning
confidence: 98%
“…More broadly, there is evidence that services trade restrictiveness is associated with weak competition in Switzerland. Rouzet and Spinelli (2016) found that heavier restrictions enable firms to charge higher mark-ups in a majority of services sectors. The authors suggest that there is scope for improving competition from trade liberalisation, especially in broadcasting (where Swiss regulation is particularly restrictive), construction, storage, and air and maritime transport.…”
Section: Foreign Trade and Investmentmentioning
confidence: 99%
“…At the same time, services trade remains overall at a less advanced stage of liberalisation than manufacturing trade (Miroudot et al, 2013;Rouzet and Spinelli, 2016;Benz, 2017). This raises the question of whether countries specialised in services would earn greater income and save more if they were able to fully exploit their comparative advantage in the global marketplace.…”
mentioning
confidence: 99%
“…15 Furthermore, apart from market access effects, services liberalisation is also likely to boost the productivity of export sectors, through a higher quality of services inputs and increased competition among domestic services suppliers (see Miroudot and Cadestin, 2017). Without prejudice to the results of the ongoing work, this paper proposes a first pass at modelling services trade liberalisation using the readily available evidence on tax equivalents of trade costs associated with the OECD STRI (Rouzet and Spinelli, 2016). Services trade liberalisation is modelled as having two complementary sides: an opening of the domestic market to services imported from abroad, and a productivity shock to the domestic services industry that could result from the opening.…”
mentioning
confidence: 99%
See 1 more Smart Citation